The parameters of infrasound effects generated by Chelyabinsk meteoroid 15 February, 2013 - Черногор, Л. Ф.; Шевелев, Н. Б. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2017)
The results of investigation of infrasound effect from Chelyabinsk meteoroid by Antarctic station which belongs Germany data are described. It`s showed that infrasound signal propagated on two distances – short and long. Via of two main methods – bandpass filtering and system spectral analysis – the delays times are defined and the arrival rates are evaluated. The prevailing periods and the durations of acoustic signals are determined. The difference between celerity of infrasound and propagation speed of sound waves are explained